Psychological and physical intimate partner violence, measured by the New York City Community Health Survey: New York City, 2018 - Alroy, Karen A. (Journal of family violence, 2023)
Purpose: Intimate partner violence (IPV) can damage long-term physical and mental health, yet IPV prevalence in New York City (NYC) is unknown. We described prevalence and health correlates of psychological and physical IPV in NYC. Method: The 2018 NYC Community Health Survey, a representative telephone survey among adult residents, asked about lifetime psychological or physical IPV experiences. We estimated age-adjusted physical and psychological prevalence, stratified by demographic variables, and created log-linear multivariable models with 95% CIs to measure the association of each IPV type with health conditions and behaviors. Results: Overall, 10,076 surveys were completed. We excluded responses with missing IPV values. Of 9,945 adults, 16.7% reported ever having experienced psychological IPV; higher prevalence among females (18.6%; CI:17.0-20.2) than males (14.5%; CI:13.1-16.2). Prevalence of not getting needed mental health treatment (PR: 4.5; CI:3.3-6.1) and current depression (PR:2.6 CI:2.1-3.1) was higher among adults who had ever experienced psychological IPV, compared with those who had not. Of 9,964 adults, 9.8% reported ever having experienced physical IPV; higher prevalence among females (12.4%; CI:11.1-13.8) than males (6.8%; CI:5.8-8.0). Prevalence of not getting needed mental health treatment (PR:3.9, CI:2.8-5.4) and current depression (PR:2.6, CI:2.1-3.2) was higher among adults who had ever experienced physical IPV, compared with those who had not. Conclusions: One in six (16.7%) and one in 10 (9.8%) NYC adults reported ever experiencing psychological IPV and ever experiencing physical IPV, respectively. Key implications suggest that IPV potentially underlies public health priority health conditions and behaviors.